Fostering Musical Education through COIL Methodology: A Higher Education Journey - Capperucci, Davide; Certini, Rossella; Maienza, Matteo; Mondéjar Muñoz, Laura; Soria Vílchez, Alejandro (Studi sulla Formazione/Open Journal of Education, 2023)
This study focuses on a design proposal for the teaching of musical and artistic subjects in Primary Education teacher training through the COIL (Collaborative Online International Learning) methodology. Firstly, a description of the theoretical basis and the educational context of the proposal is given, followed by a presentation of the application of the project, the tools and materials used. Then, the implementation of this proposal with the students is presented, as well as other questions that emerged during the design process. Finally, the results obtained after its implementation and reflected in the evaluation survey of the participating students are shared. The objective is to enrich the data on the benefits of the application of this methodology at university level.